Crystallization and preliminary X-ray crystallographic analysis of highly thermostable L2 lipase from the newly isolated Bacillus sp. L2 - Mohd Shariff, Fairolniza; Raja Abdul Rahman, Raja Noor Zaliha; Mohamad Ali, Mohd Shukuri; Leow, Adam Thean Chor; Basri, Mahiran; Salleh, Abu Bakar (International Union of Crystallography, 2010)
Purified thermostable recombinant L2 lipase from Bacillus sp. L2 was crystallized by the counter-diffusion method using 20% PEG 6000, 50 mM MES pH 6.5 and 50 mM NaCl as precipitant. X-ray diffraction data were collected to 2.7 Å resolution using an in-house Bruker X8 PROTEUM single-crystal diffractometer system. The crystal belonged to the primitive orthorhombic space group P212121, with unit-cell parameters a = 87.44, b = 94.90, c = 126.46 Å. The asymmetric unit contained one single molecule of protein, with a Matthews coefficient (V M) of 2.85 Å3 Da−1 and a solvent content of 57%.